High molecular weight DNA extraction methods lead to high quality filamentous ascomycete fungal genome assemblies using Oxford Nanopore sequencing. Issue 4 (19th April 2022) - Petersen, Celine; Sørensen, Trine; Westphal, Klaus R.; Fechete, Lavinia I.; Sondergaard, Teis E.; Sørensen, Jens L.; Nielsen, Kåre L.
Abstract : During the last two decades, whole-genome sequencing has revolutionized genetic research in all kingdoms, including fungi. More than 1000 fungal genomes have been submitted to sequence databases, mostly obtained through second generation short-read DNA sequencing. As a result, highly fragmented genome drafts have typically been obtained. However, with the emergence of third generation long-read DNA sequencing, the assembly challenge can be overcome and highly contiguous assemblies obtained. Such attractive results, however, are extremely dependent on the ability to extract highly purified high molecular weight (HMW) DNA. Extraction of such DNA is currently a significant challenge for all species with cell walls, not least fungi. In this study, four isolates of filamentous ascomycetes ( Apiospora pterospermum, Aspergillus sp . (subgen. Cremei ), Aspergillus westerdijkiae, and Penicillium aurantiogriseum ) were used to develop extraction and purification methods that result in HMW DNA suitable for third generation sequencing. We have tested and propose two straightforward extraction methods based on treatment with either a commercial kit or traditional phenol-chloroform extraction both in combination with a single commercial purification method that result in high quality HMW DNA from filamentous ascomycetes. Our results demonstrated that using these DNA extraction methods and coverage, above 75 x of our haploid filamentous ascomycete fungal genomes result in complete and contiguous assemblies.